1996
DOI: 10.1111/j.1476-5381.1996.tb15348.x
|View full text |Cite
|
Sign up to set email alerts
|

Antiarrhythmic action of rilmenidine on adrenaline‐induced arrhythmia via central imidazoline receptors in halothane‐anaesthetized dogs

Abstract: To elucidate the role of central imidazoline receptors in the genesis of adrenaline‐induced arrhythmias under halothane anaesthesia, we investigated the effects of rilmenidine, a selective agonist at imidazoline receptors, on this type of arrhythmia in dogs. Rilmenidine (1, 3, 10 μg kg−1, i.v.) did not affect basal haemodynamic parameters (heart rate and blood pressure), but dose‐dependently inhibited adrenaline‐induced arrhythmias under halothane anaesthesia. Although, rilmenidine has a weak affinity for α2‐a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
13
0

Year Published

1998
1998
2011
2011

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(16 citation statements)
references
References 32 publications
3
13
0
Order By: Relevance
“…In fact, rilmenidine was able to blunt centrally induced ventricular arrhythmias through the inhibition of sympathetic hyperactivity in an experimental model of pharmacological activation of the central nervous system with bicuculline in anesthetized rabbits (21). Moreover, rilmenidine dose-dependently inhibits adrenaline-induced arrhythmias under halothane anesthesia in dogs, acting on central imidazoline receptors (22). These investigators suggested that the antiarrhythmic properties of rilmenidine in this particular experimental model result, at least in part, from simultaneous increases in vagal tone and baroreceptor sensitivity (22).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In fact, rilmenidine was able to blunt centrally induced ventricular arrhythmias through the inhibition of sympathetic hyperactivity in an experimental model of pharmacological activation of the central nervous system with bicuculline in anesthetized rabbits (21). Moreover, rilmenidine dose-dependently inhibits adrenaline-induced arrhythmias under halothane anesthesia in dogs, acting on central imidazoline receptors (22). These investigators suggested that the antiarrhythmic properties of rilmenidine in this particular experimental model result, at least in part, from simultaneous increases in vagal tone and baroreceptor sensitivity (22).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, rilmenidine dose-dependently inhibits adrenaline-induced arrhythmias under halothane anesthesia in dogs, acting on central imidazoline receptors (22). These investigators suggested that the antiarrhythmic properties of rilmenidine in this particular experimental model result, at least in part, from simultaneous increases in vagal tone and baroreceptor sensitivity (22). Using an identical experimental model, Hayashi et al (23) demonstrated that the arrhythmogenic dose of adrenaline decreases in a dose-dependent manner only after treatment with a 2 -adrenoceptor antagonists with an imidazoline structure but not with non-imidazoline antagonists such as yohimbine.…”
Section: Discussionmentioning
confidence: 99%
“…Rilmenidine dose dependently inhibits adrenaline-induced dysrhythmias under halothane anaesthesia in dogs [41]. This action was blocked by bilateral vagotomy and by pretreatment with a nonspecific alpha-2 adrenoceptor and imidazoline receptor antagonist idazoxan intracisternally.…”
Section: Historymentioning
confidence: 91%
“…Beyond its well known properties, a recent study has shown that dexmedetomidine has potential antiarrhythmic properties and can be used for the acute treatment of pediatric supraventricular tachyarrhythmias including junctional ectopic, atrial ectopic and reentrant type tachycardias [7]. In addition, animal studies have demonstrated that activation of imidazoline and alpha-2 adrenoceptors in the central nervous system, prevents adrenaline-induced ventricular tachycardia and that stimulation of the vagus nerve may be critical for this antiarrhythmic effect [811]. …”
Section: Introductionmentioning
confidence: 99%